Towards some types of word combinations in a compound subordinate clause - Burchuladze, Tea (The Kartvelologist - A Bilingual Peer-reviewed, Academic Journal of Georgian Studies, 2016)
The issue regarding word-combinations in subordinate clauses with the following subordinating conjunctions as if, although/even though, because/since, even if/even, while, or else/otherwise, before/until/till, as though, even (if), that, if is interesting to explore. These conjunctions establish a meaningful correlation with the verb-predicate and in this way create word combinations: While they were caressing each other …; While he was…; since I had…; otherwise I should have killed…; Even you tell me…; Even if a killer would have hold…; though they respected …; as if there was… In these word-combinations a subordinating conjunction agrees only with the verb-predicate. In such cases there is a correlation similar to an amorphous word (adverb or prepositional nouns) and the predicate referred to as parataxis. Contextually, the verb-predicate is linked to the given subordinating conjunctions so that it does not possess any grammatical function.A similar type of word-combination occurs between subordinating conjunctions and the verb-predicate, similar to the type existing between amorphous adverbs and the predicate. From the given subordinating conjunctions as if and as though are particles and they cannot form a syntactic relation with the word to which they are added. However, in the given sentences they are subordinating conjunctions and not particles. Due to this, similar to other subordinating conjunctions (so –as if, so – as though), together with a correlative word they also link with each other the parts of the subordinate clause as in the case of other subordinating conjunctions (as though, as if) . Therefore, I propose that they create word-combinations together with the corresponding verb-predicate in a hypotactic sentence. Obviously, this is not true in the case of singling out word-combinations in a simple sentence, because being particles and not conjunctions, the subordinating conjunctions if, thatcannot create word-combinations with the verb-predicate. The reason for this is that they do not relate to one member of the sentence, but to the whole sentence (the main clause). Being conjunctions they cannot create a syntagm.